The differential futures of ski tourism in Ontario (Canada) under climate change: the limits of snowmaking adaptation. Issue 11 (3rd July 2019) - Scott, Daniel; Steiger, Robert; Rutty, Michelle; Pons, Marc; Johnson, Peter
Abstract : The international ski tourism industry is highly vulnerable to inter-annual climate variability and climate change. Accordingly, there is a strong need to advance our understanding of climate risk for this multi-billion tourism market that is so important to mountain regions around the world. This study addressed major limitations in the ski tourism literature, while concurrently supporting priority information needs of ski tourism stakeholders. An improved version of SkiSim 2.0 is applied to all 34 alpine ski areas in southern Ontario (Canada) to examine potential changes in the capacity of this regional marketplace. Model improvements include differential snowmaking capacities of individual ski areas, updated snowmaking decision rules, as well as a new indicator, termed 'terrain-days', to estimate changes in system capacity. The results project two fundamentally different futures for this ski tourism marketplace under climate change. If the international community succeeds in achieving the + 2°C Paris Agreement policy goal, then losses in system capacity can be limited to less than 10% in the mid- and late-century. In contrast, a high-end emission scenario (RCP 8.5) would severely disrupt this ski tourism market by mid-century, with system capacity losses between 28% and 73%.